1997
DOI: 10.1136/hrt.77.2.154
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular sequelae of toxaemia of pregnancy.

Abstract: Objective-To determine whether the rate of cardiovascular disease is different among parous women with a general practitioner reported history of toxaemia of pregnancy than among those not reported to have experienced toxaemia, or among nuliparous women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
124
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(133 citation statements)
references
References 16 publications
8
124
0
1
Order By: Relevance
“…In a study of 374 women with a history of hypertensive complications in pregnancy, the risk of dying from CHD (risk ratio 2.61; 95% CI 1.11-6.12) was significantly higher among women who had had eclampsia or pre-eclampsia (risk ratio 1.90; 95% CI 1.02-3.52) than among those with hypertension alone [17]. The Royal College of General Practitioners' oral contraceptive study also reported that a history of preeclampsia increased the risk of cardiovascular conditions in later life (relative risk for future ischaemic heart disease 1.7; 95% CI 1.3-2.2) [18], and a record linkage study from Scotland has also recently reported an association between pre-eclampsia and later ischaemic heart disease in the mother (risk ratio 2.0; 95% CI 1.5-2.5) [19]. An important clinical implication of our findings and these other studies linking pre-eclampsia to future ischaemic heart disease is whether this finding can identify women 'at risk' who otherwise might not have been identified, or whether the use of established risk factors such as hypertension and obesity would have identified these 'at risk' women and offered an opportunity for primary prevention.…”
Section: Discussionmentioning
confidence: 85%
“…In a study of 374 women with a history of hypertensive complications in pregnancy, the risk of dying from CHD (risk ratio 2.61; 95% CI 1.11-6.12) was significantly higher among women who had had eclampsia or pre-eclampsia (risk ratio 1.90; 95% CI 1.02-3.52) than among those with hypertension alone [17]. The Royal College of General Practitioners' oral contraceptive study also reported that a history of preeclampsia increased the risk of cardiovascular conditions in later life (relative risk for future ischaemic heart disease 1.7; 95% CI 1.3-2.2) [18], and a record linkage study from Scotland has also recently reported an association between pre-eclampsia and later ischaemic heart disease in the mother (risk ratio 2.0; 95% CI 1.5-2.5) [19]. An important clinical implication of our findings and these other studies linking pre-eclampsia to future ischaemic heart disease is whether this finding can identify women 'at risk' who otherwise might not have been identified, or whether the use of established risk factors such as hypertension and obesity would have identified these 'at risk' women and offered an opportunity for primary prevention.…”
Section: Discussionmentioning
confidence: 85%
“…The lower endogenous estrogen level is consistent with a lower HDL cholesterol level and with heart disease [18]. Hypertensive disorders of pregnancy have been reported to be more common in younger mothers [19] who have a known risk of long-term CVD [20][21][22]. Further studies are needed to explain the mechanisms behind the increasing risk of CVD with earlier age at first delivery.…”
Section: Discussionmentioning
confidence: 87%
“…Women who develop HDP have an increased risk of ischemic heart disease (11-16), hypertension (12,15), stroke (14,15), venous thromboembolism (13,17), and mortality (14,16,18) over the long term. Greater weight gain, and the increased risk of overweight and obesity in middle age, is associated with an increased risk of cardiovascular disease, diabetes, cancers, and overall mortality (19)(20)(21)).…”
Section: Discussionmentioning
confidence: 99%